Modelling of Diesel Generator Sets That Assist Off-Grid Renewable Energy Micro-grids - Johanna Salazar; Fernando Tadeo; Cesar Prada (Renewable Energy and Sustainable Development)
This paper focuses on modelling diesel generators for off-grid installations based on renewable energies. Variations in Environmental Variables (for example, Solar Radiation and Wind Speed) make necessary to include these auxiliary systems in off-grid renewable energy installations, in order to ensure minimal services when the produced renewable energy is not sufficient to fulfill the demand. This paper concentrates on modelling the dynamical behaviour of the diesel generator, in order to use the models and simulations for developing and testing advanced controllers for the overall off-grid system. The Diesel generator is assumed to consist of a diesel motor connected to a synchronous generator through an electromagnetic clutch, with a flywheel to damp variations. Each of the components is modelled using physical models, with the corresponding control systems also modelled: these control systems include the speed and the voltage regulation (in cascade regulation).